Analisis Metafungsi Bahasa dalam Lagu “The Greatest Love Of All” Karya Whitney Houston melalui Kerangka Kerja Halliday - Rahayu, Eka Puji; Puspitasari, Dewi; Widyaningrum, Agnes (Dinamika Bahasa dan Budaya, 2025)
This study examines Whitney Houston’s song “The Greatest Love of All” through the Systemic Functional Linguistics (SFL) lens, focusing on the ideational, interpersonal, and textual metafunctions outlined by M.A.K. Halliday. The analysis, employing a qualitative methodology, reveals how the lyrics articulate self-empowerment, personal growth, and societal responsibility themes. The ideational metafunction emphasizes the representation of encounters, such as the significance of sustaining future eras and grasping self-love and its transformative potential. The interpersonal metafunction highlights the relationship flow between the singer and the gathering of people, utilizing a high disposition of revelation and methodology to motivate certainty and specialization. In the meantime, the printed metafunction ensures topical coherence and consistency through structural harmony. Thus, revealing the etymological processes in the song, this thought demonstrates how music acts as a powerful means of expressing the passionate and ideological messages that resonate within it. Keywords: Systemic Functional Linguistics (SFL), Language Metafunctions, Self-Improvement, Lyric Analysis, Ideological Messages in Music